USM TO FOCUS ON CROSS COLLABORATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 11 May 2016 Universiti Sains Malaysia (USM) would be focusing mainly on cross collaborations to enhance research and innovation efforts as well as academics in the future.This was said by the USM ViceChancellor, Professor Dato' Dr. Omar Osman in concluding his visit to the Czech Republic and to several universities in the United Kingdom recently.